Factors Affecting Students' Interest in Entrepreneurship - Novita Maulidya Jalal (MultiTech Publisher, 2023)
The aim of this research is to describe the factors that influence students' entrepreneurial interest. The method in this research is a literature study with descriptive methods. The journals used in this research consisted of 9 journals with similar research themes, namely factors that influence students' interest in entrepreneurship. The results obtained in this research are that students' interest in entrepreneurship can develop due to two factors, namely internal factors and external factors. Internal factors include personal (internal), university, external and information, self-efficacy, freedom to work, visionary, expertise. Considering that universities have quite a large influence, entrepreneurship courses and programs in universities should be made as good as possible to foster entrepreneurial interest among students. Besides, the values ​​and encouragement that individuals have regarding the social conditions around them will trigger them to think and do something. The implication of this research is to provide knowledge of factors that can support the formation of interest in entrepreneurship in students.